PENGARUH PENAMBAHAN SUPERPLASTISIZER TERHADAP CAMPURAN BETON RINGAN YANG MENGGUNAKAN STYROFOAM - Kusnadi Kusnadi; Dewi Sulistyorini (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
The risk of failure of structures effect of earthquake be high due to the heavyvolume of concrete has a fairly high (2400 kg/m3). Advances in technology and theimpact of the economic crisis encourage construction of infrastructure use concretemasonry units under 1900 kg/m3 in weight. The use of lightweight concrete is thefiller material styrofoam intend at non structural components like wall. One of theproblem of making lightweight concrete using styrofoam is the low value of slump, sothat the mix becomes difficult (low workability). It is therefore necessary to addmaterial superplastisizer This research used 20 cylinder test samples. Thecomposition of the mixture consists of sand, cement and grain of styrofoam. Thestyrofoam in concrete is 20% in volume. The Sample variation consists of lightweight concrete using styrofoam without superplastisizer is four cylinder, with addedsuperplastisizer four cylinder were 0.5%, 1.0%, 1.5% and 2%, respectively in weightof cement. The results showed the addition of superplastisizer 0.5%, 1%, 1.5% and2% of the cement weight increases the value of slump were 100%, 183%, 216% and507% respectively. The addition of superplastisizer 0.5%, 1%, 1.5% and 2% of thecement weight increase ceompression strength were 8.48% 4.25%, 12.67% and17.37% respectively. The addition of superplasticizer will increases the slump for thesame water content in fresh concrete, so can increase the compressive strength ofconcrete cylinder.Keyword : beton styrofoam, workabilitas, superplasticizer